De Skandinaviske og arktiske Amphipoder - Boeck, Axel, 1833-1873.; Boeck, Hakon, 1832- (Christiania : trykt hos A. W. Brøgger, 1872)
Includes handwritten annotations and index. Text and plates. Mode of access: Internet.